Viscosity, Total Acid, Protein and Hedonic Level of Kefir Made from Buffalo Milk with Different Concentration of Kefir Grain - Jethro Rafande Manurung; Heni Rizqiati; Valentinus Priyo Bintoro (Journal of Applied Food Technology, 2022)
This research aims to determine the effect of different kefir grain concentration to viscosity, total acid, protein and hedonic level of buffalo milk kefir and to determine the ideal kefir grain concentration for buffalo milk kefir. The basic ingredients used in this research were buffalo milk and kefir grain. Concentration of kefir grain at 2.5%, 5%, 7.5%, 10% (g/v) was used to measure viscosity, total acid, protein and hedonic level of buffalo milk kefir. Ostwald pipette and pycnometer were used to determine the viscosity, total acid used titration method with NaOH 0.1 N, destruction and distillation methods were used to determine the protein content and the hedonic test were done by 25 panelists. The results show that different levels of kefir grain concentration gave significant effect (p<0.05) on every parameter. Various levels of kefir grain concentration had highly significant effect (p<0.05) on kefir as a product. The conclusions from this study are the more addition of kefir grain, the more viscosity, total acid, and protein content. From the hedonic test gave specific results in sour taste, aroma, texture and overall.